Complete pathological response with diabetic ketoacidosis to the combination of sintilimab and anlotinib in an unresectable hepatocellular carcinoma patient: a case report. Issue 1 (January 2022) - Fu, Lingli; Chen, Ping; Wang, Shijie; Liu, Wenmin; Chen, Zubing; Chen, Hongbin; Fu, Zhenming
Abstract : Most hepatocellular carcinoma (HCC) patients have dismal prognoses because they are already in the advanced stage at the time of initial diagnosis and are unable to undergo upfront surgery. Recent studies of immune checkpoint inhibitors (ICIs) and antiangiogenic agents (AAAs) have shown encouraging results for unresectable HCC (uHCC). Here, we report a patient with uHCC who was treated with a combination of anlotinib and sintilimab (sintilimab 200 mg, intravenous glucose tolerance test, q21d and anlotinib 12 mg, orally, d1–14, q21d), an analog of the combination of lenvatinib and pembrolizumab with much lower cost. The patient with recurrent uHCC was downstaged to resectable disease by the combination therapy. After eight cycles of treatment with anlotinib and sintilimab, the patient underwent a second operation. The histology of the resected mass revealed a major and almost complete pathological response. However, this patient was diagnosed with type I diabetes mellitus with ketoacidosis after nearly 10 cycles of combination treatment with anlotinib and sintilimab. Active follow-ups revealed no signs of local recurrence or distant failure. In conclusion, this case report demonstrated that the combination of anlotinib and sintilimab, one of the strategies combining ICIs with AAAs, showed promising efficacy in the treatment of uHCC patients.